Synthesis and Activity Test of Cu/ZnO/Al2O3 for the Methanol Steam Reforming as a Fuel Cellâs Hydrogen Supplier - IGBN Makertihartha; Subagjo Subagjo; Melia Laniwati Gunawan (Journal of Engineering and Technological Sciences, 2009)
The  synthesis  of  hydrogen  from  hydrocarbons  through  the  steam reforming  of  methanol  on  Cu/ZnO/Al2O3  catalyst  has  been  investigated.  This process is assigned to be one of the promising alternatives for  fuel cell hydrogen process source. Hydrogen synthesis from methanol can be carried out by means of  methanol  steam  reforming  which  is  a  gas  phase  catalytic  reaction  between methanol and water. In this research, the  Cu/ZnO/Al2O3  catalyst  prepared by the dry  impregnation  was  used.  The  specific  surface  area  of  catalyst  was  194.69 m2/gram.The  methanol  steam  reforming  (SRM)  reaction  was  carried  out  by means of the injection of gas mixture containing methanol and water with 1:1.2 mol ratio and 20-90 mL/minute feed  flow rate to a fixed bed reactor loaded by 1 g of catalyst. The reaction temperature was 200-300 °C, and the reactor pressure was 1 atm. Preceding  the reaction, catalyst was reduced in the H2/N2  mixture at 160  °C.  This  study  shows  that  at  300  °C  reaction  temperature,  methanol conversion  reached  100%  at  28  mL/minute  gas  flow  rate.  This  conversion decreased  significantly  with  the  increase  of  gas  flow  rate.  Meanwhile,  the catalyst prepared for SRM  was stable in 36 hours of operation at 260  °C. The catalyst exhibited a good stability although the reaction condition was shifted to a higher gas flow rate.